Crop yield and water use efficiency in response to long-term diversified crop rotations - Cui, Zhengjun; Yan, Bin; Gao, Yuhong; Wu, Bing; Wang, Yifan; Xie, Yaping; Xu, Peng; Wang, Haidi; Wen, Ming; Wang, Yingze; Ma, Xingkang (Frontiers in Plant Science, 2022)
Crop production and water productivity may be impacted by diverse crop rotation and management practices. A field study was conducted from 2017-2020 in the Loess Plateau to evaluate the effects of crop rotation sequences on pre-planting and post-harvest soil water storage (SWS), annualized crop yield, water use, and water productivity. Crops in rotation included oil flax (Linum usitatissimum L.) (F), wheat (Triticum aestivum L.) (W), potato (Solanum tuberosum L.) (P). Twelve 4-year-cycle crop rotation treatments, along with a continuous oil flax treatment as a baseline, were included. The results showed that the average soil water content under the 0-150 cm soil layer in all treatments was increased after one rotation cycle, and the PWFW treatment achieved the highest SWC (17.1%). The average soil water storage (winter fallow season) and evapotranspiration (ETa) (growing season) under different crop rotation sequences were lower than those under continuous oil flax cropping. The ETa of FFFF increased by 28.9, 2.7, 15.3, and 28.4%, compared to average crop rotations in 2017, 2018, 2019, and 2020, respectively. Crop rotation had a significant effect on average annual yield and water use efficiency (WUE), which varied by year and rotation sequence. The crop rotations with the highest grain yield of oil flax were FFWP (2017), WFWP (2018),WPFF (2019) and FWPF (2020); the grain yield of wheat was highest when the two pre-crops (previously cultivated crops) were F-F, and potato yield was highest when the two pre-crops were W-F (except 2018). On average, the WUE of oil flax was was 8.6, 38.7, 22.7, and 42.1% lower with FFFF than other diversity crop rotations in 2017, 2018, 2019, and 2020. We found that the WUE was not the largest when the grain yield of oil flax and wheat was highest. The treatments with maximum grain yield and WUE were not consistent. Our findings also revealed that wheat-potato-oil flax or potato-wheat-oil flax rotation could increase oil flax grain yields while wheat-oil flax-potato-oil flax markedly improved oil flax WUE.